A study of table tennis player sport passion effect mode - Lu, C.-J.; Nai, H.-F.; Chen, S.-S. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
Objective: This study is to explore the Table Tennis Sport Passion Effect Mode. Method: With the Literature review, the questionnaire of Sport Passion Effect Mode, item analysis and exploratory factor analysis were used to examine the CR value and structure of the factors. Finally, the confirmatory factor analysis was used to examine the hypothetical measurement model, and furthermore examine the scale`s difference validity. Results: Through the statistical verification of structural equation modelling, the overall model fit well ÷2=94.67, df=62, ÷2/df=1.53, RMSEA=0.047, CFI=0.98. Conclusion: The Sport Passion Effect Mode is a measuring tool with the empirical study, and the follow-up researchers can use the scale that in built in this study for the further related research.